Integrasi Dan Revitalisasi Poskesdes Menjadi Posyandu Prima di Kampung Saptomulyo Kotagajah Lampung Tengah - Islamiyati Islamiyati; Sadiman Sadiman; Yoga Tri Wijayanti (Universitas Kristen Indonesia Toraja, 2024)
One of the health transformation programs by the Indonesian Ministry of Health is the transformation of the primary health care system. One form of integrated transformation of primary health services is by establishing prime posyandu. Posyandu Prima is a revitalization program for posyandu or poskesdes or supporting community health centers that already exist in the village. Saptomulyo village does not have a supporting community health center but does have a village health post. The aim of this community service is to revitalize existing posyandu and village health posts so that they become prime posyandu with the hope of improving the health status of the people of Saptomulyo Village.Methods for implementing activities include: Coordination with village officials using the brainstorming method, Formation of a prime posyandu organization using brainstorming and discussions, recruitment of cadres with interviews and discussions with candidates, training of cadres and community health center officers/nurses/midwives with lectures, questions and answers, discussions and demonstrations, as well as collecting public health data in Saptomulyo Village using surveys .The result of the activity was the implementation of Posyandu Prima socialization/training activities for Posyandu Prima cadres and administrators as well as health posyadu cadres and all participants were declared to have passed. There are prime posyandu locations and buildings ready to open services